2008
DOI: 10.1210/me.2007-0561
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-Induced Proteolytic Reduction in Hepatic Growth Hormone (GH) Receptor: A Novel Mechanism for GH Insensitivity

Abstract: GH is an important anabolic hormone. We previously demonstrated in cell culture that the cell surface GH receptor (GHR) is susceptible to inducible metalloproteolytic cleavage that yields the shed receptor extracellular domain (called GH binding protein) and renders the cells desensitized to subsequent GH stimulation. Sepsis and inflammatory states are associated with hepatic desensitization to GH, although disparate mechanisms have been postulated in various animal models. Using C3H/HeJ mice, we now demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 65 publications
3
21
0
1
Order By: Relevance
“…information from both animal models and human studies supports each of these potential mechanisms ( Figure 3). 14,15,49,50,[52][53][54][55][56][57][58][59][60][61][62][63][64] IGF-I-independent mechanisms inflammatory cytokines inhibit linear growth through pathways other than iGFi production. animal experi ments have shown that tnF and il1 increase chondro cyte death and thus may have a deleterious effect on growth.…”
Section: Key Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…information from both animal models and human studies supports each of these potential mechanisms ( Figure 3). 14,15,49,50,[52][53][54][55][56][57][58][59][60][61][62][63][64] IGF-I-independent mechanisms inflammatory cytokines inhibit linear growth through pathways other than iGFi production. animal experi ments have shown that tnF and il1 increase chondro cyte death and thus may have a deleterious effect on growth.…”
Section: Key Pointsmentioning
confidence: 99%
“…54 Both mechanisms are seemingly independent of the inflammatory cytokine cascade, and the addition of antitnF antibody failed to abrogate this effect. 52 although certainly intriguing, the clinical signifi cance of these findings and their rela tive importance as a mechanism in the setting of growth impairment and Crohn's disease is yet to be determined.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrancy of the TLR signaling system may therefore regulate chronic inflammation in IBD. Moreover, our recent murine studies have shown that LPS can directly suppress growth hormone (GH) signaling, by inducing proteolytic degradation of the hepatic GH receptor (GHR) (18). LPS may therefore also contribute directly to linear growth failure in children with CD.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, a pesar de estos resultados, es posible que otros mecanismos sean los responsables de los cambios de GH inducido por LPS. Wang et al (28), en una investigación in vivo en ratones, reportaron que LPS inducen insensibilización de GH a través de la proteólisis de su receptor (GHR).…”
Section: Introductionunclassified